2019
DOI: 10.1007/s00114-019-1605-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating monitoring options for conservation: comparing traditional and environmental DNA tools for a critically endangered mammal

Abstract: While conservation management has made tremendous strides to date, deciding where, when and how to invest limited monitoring budgets is a central concern for impactful decision-making. New analytical tools, such as environmental DNA (eDNA), are now facilitating broader biodiversity monitoring at unprecedented scales, in part, due to time, and presumably cost, of methodological efficiency. Genetic approaches vary from conventional PCR (cPCR; species presence), to metabarcoding (community structure), and qPCR (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 50 publications
(65 reference statements)
0
52
0
1
Order By: Relevance
“…Depends on assays, the qualitative method may have limited resolution to species diversity and are sometimes sensitive up to family level 20,21 . On the other hand, quantitative methods using qPCR on certain species not only can detect the presence of the target species, but also infers the relative abundance of the species in the environment, which complements the limitation of metabarcoding analysis 5,22 . In open oceans, the eDNA concentrations are often low, and filtering large volumes of water is required to accumulate sufficient amounts of eDNA.…”
Section: Discussionmentioning
confidence: 99%
“…Depends on assays, the qualitative method may have limited resolution to species diversity and are sometimes sensitive up to family level 20,21 . On the other hand, quantitative methods using qPCR on certain species not only can detect the presence of the target species, but also infers the relative abundance of the species in the environment, which complements the limitation of metabarcoding analysis 5,22 . In open oceans, the eDNA concentrations are often low, and filtering large volumes of water is required to accumulate sufficient amounts of eDNA.…”
Section: Discussionmentioning
confidence: 99%
“…Detection and monitoring of rare, cryptic, and endangered species using conventional techniques is a difficult task that often involves huge amounts of time and effort (Qu & Stewart 2019b).…”
Section: Detecting Rare Cryptic or Endangered Speciesmentioning
confidence: 99%
“…Studies that have quantitatively assessed the cost-efficiency of eDNA relative to traditional methods suggest that eDNA sampling is relatively cheaper than traditional surveys (Biggs et al 2015;Davy et al 2015;Huver et al 2015;Sigsgaard et al 2015a;Qu & Stewart 2019a), although this can depend on the target taxa, site-specific detection rates, budgets, and other considerations (Smart et al 2016). For instance, Qu & Stewart (2019) found that the cost of detecting and quantifying Yangtze finless porpoise (Neophocaena asiaeorientalis asiaeorientalis) populations using visual surveys was 1.41-1.88 times (monthly cost) and 4.22-5.64 times (seasonal cost) higher than using eDNA.…”
Section: Challenges and Limitations Of Ednamentioning
confidence: 99%
“…We did not have the option for more sensitive qPCR or ddPCR, yet our applied end-point nPCR approach is known to lead to reliable detections (Nathan et al, 2014;Davison et al, 2019). Furthermore, end-point PCRs can have low detection limits (e.g., Qu and Stewart, 2017), which is why we considered that our results were more impacted by low detection rates than cross-contamination.…”
Section: Dispersal Of the Rhine Sculpinmentioning
confidence: 99%